Research on the invulnerability of regional network based on topology analysis - Changqing AN; Yujia LIU; Hui WANG; Zhiyan ZHENG; Tao YU; Jilong WANG (Tongxin xuebao)
To measure the overall impact of different attacks a network region may encounter, an evaluation algorithm can be used to capture the difference in invulnerability of regional network topologies.Specifically, the vulnerability of regional network and that of connection topology between regions both internally and externally was analyzed.To find predictions between regions as supplemental topology data and create the Internet topology, data would be measured in various ways and verified.Using stratified probability sampling, multiple damage simulations could predict the worst-case scenarios in real conditions.Damage was simulated multiple times based on stratified probability sampling to approximate the damage situation of the area under real conditions.A significance tester was realized to measure the impact of damage from the overall level and special weak points respectively, discover the difference of the damage between the areas, and calculate the regional invulnerability ranking.Finally, the ranking and clustering results of forty-eight regions were given.